Molecular dynamics of trans-cis isomerization in bathorhodopsin. - Birge, R R (1981)
Semiempirical molecular dynamics procedures are used to theoretically investigate the trajectories and quantum yields of the rhodopsin leads to bathorhodopsin and bathorhodopsin leads to rhodopsin photoisomerizations. The calculations are based on the semiclassical trajectory formalism and rhodopsin binding site model proposed by Birge and Hubbard (1980. J. Am. Chem. Soc. 102: 2195-2205). The rhodopsin leads to bathorhodopsin photoisomerization is predicted to occur in approximately 2.2 ps with a quantum yield of 0.62 in reasonable agreement with experiment (less than 6 ps, phi = 0.67). The bathorhodopsin leads to rhodopsin photoisomerization is predicted to occur in approximately 1.8 ps with a quantum yield of 0.48. The latter number is in good agreement with the observed quantum yield for cattle bathorhodopsin (phi = 0.5) but in poor agreement with the observed value for squid bathorhodopsin (phi = 0.36). Our calculations suggest that the observed photochemical preference of the chromophore in cattle bathorhodopsin to isomerize to form rhodopsin (phi = 0.5), instead of isorhodopsin (phi - 0.054), is associated with a significant out-of-plane distortion (9-17 degrees) of the 11,12-trans dihedral angle in the batho chromophore.